Emphasizing the Rising Importance of Digital Technologies for Delivery of Accounting Services - Adrian Isip (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- How is the accounting profession engaging with digitalization for delivery of services? How is digital transformation of accounting firms impacted by the Covid-19 outbreak? Motivation- Nowadays information and communication technologies are vital for companies to carry out their business operations. In a dynamic business environment, the speed of information production, the accuracy, immediate access to information, instant communication and electronic data transfer are crucial. In times of crisis, characterized by uncertainty, social and economic imbalances, managers need the financial and non-financial information much faster, more frequent and with a higher level of detail in order to make prompt decisions and ensure the business continuity. Idea- I investigate the rising importance of digital technologies for delivery of accounting services using the theory of change as theoretical framework in the context of Covid-19 pandemic as a strong pressure that forced the companies to accelerate their digitalization process. Data and tools- My methodological approach involves a qualitative analysis of data collected from semi-structured interviews with 21 professionals working within accounting firms. Findings- Following the theory of change, the results indicated that Covid-19 pandemic put high pressure on people to change their perceptions and behaviour and they adapted quite well and fast to the new reality characterized by social distancing. Digital technologies played a key role in helping organizations to carry on their activities and overcome the people's resistance to the changes related to work, mobility and social interactions. According to the conceptual model, digitalization process within the companies was accelerated and digital transformation was achieved by engaging technologies, employees and clients. Some companies embraced outsourcing due to the loss of staff and the need to save money. Several accounting firms implemented telework and they exchanged documents and reports with their clients in cloud. The use of digital technologies enabled many accounting firms to gain new clients located in other cities. Moreover, some accounting firms adopted robotic process automation and even hired remote professionals from other cities because of labour shortage. Contribution- This research complements the literature related to digitalization in accounting and outsourcing of accounting services due to Covid-19 outbreak. Digital technologies have opened new avenues for outsourcing of accounting services and helped some companies to overcome their shortage of professionals. Practical implications- This study has implications for accounting firms, employees and clients since the use of digital technologies removed the physical location constraints and brought remote collaboration opportunities.
Keywords: M41; M55; O33; 650; cloud accounting; robotic process automation; online meeting applications; accounting outsourcing; remote services; telework